Transcriptomic analysis of the signature of neurogenesis in human hippocampus suggests restricted progenitor cell progression post-childhood. (December 2020) - Kumar, Ashutosh; Pareek, Vikas; Faiq, Muneeb A.; Kumar, Pavan; Kumari, Chiman; Singh, Himanshu N.; Ghosh, Sanjib K.
Graphical abstract: Highlights: NESTIN, SOX1, and SOX4 decreased progressively from prenatal to adult age. KI67 and TBR2 reached zero expression level at adolescence. NEUROD1, DCX, PSA NCAM remained unchanged post-childhood. VEGF and FGF2 did not change significantly from prenatal to adult age. BAX and TP53 decreased progressively from prenatal to adult age. Abstract: Purpose: Immunohistological investigations have given rise to divergent perspectives about adult hippocampal neurogenesis in humans. Therefore, this study aimed to examine whether a comprehensive transcriptomic analysis of signature markers of neurogenesis, supplemented with markers of gliogenesis, vasculogenesis, cell proliferation, and apoptosis, may help discern essential aspects of adult hippocampal neurogenesis in humans. Materials and Methods: RNA expression data for salient marker genes of neurogenesis, gliogenesis, vasculogenesis, and apoptosis in post-mortem human hippocampal tissue [from prenatal (n = 15), child (n = 5), adolescent (n = 4), and adult (n = 6) brains] were downloaded from the Allen Human Brain Atlas database (http://www.brainspan.org/rnaseq/search/index.html ). Gene expression data was categorized, median values were computed, and age group-specific differential expression was subjected to statistical analysis (significance level, α = 0.01). Results: With the exception of the genes encoding GFAP, BLBP, SOX2, and PSA-NCAM (unchanged), and the post-mitotic late maturation markers CALB1, CALB2, MAP2, and NEUN as well as the pan-neuronal marker PROX1 which were persistently expressed throughout, expression of all other genes associated with neurogenesis was steeply and progressively downregulated between perinatal life and adulthood. Interestingly, expression of the classical proliferation marker KI67 and a progenitor cell marker TBR2 were found to have reached baseline expression levels (zero expression score) at adolescence while the expression of immature neuronal, post-mitotic early and late maturation markers remained at a constant level after childhood. In contrast, markers of gliogenesis (other than PDGFRA and Vimentin ) were significantly upregulated between prenatal life and childhood. Expression of the vasculogenesis markers VEGFA and FGF2 did not differ across any of the age groups studied, whereas the expression of apoptotic markers was progressively decreased after prenatal life. Conclusions: Our findings indicate that the progression of neurogenesis from progenitor cells is highly restricted in the human brain from childhood onwards. An alternative possibility that limited neurogenesis may be continued in adolescents and adults from a developmentally arrested pool of immature neurons needs to be examined further through experimental studies.